1998
DOI: 10.1109/10.650355
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution technique for multidimensional NMR spectroscopy

Abstract: Abstract-In this paper, a scheme for estimating frequencies and damping factors of multidimensional nuclear magnetic resonance (NMR) data is presented. multidimensional NMR data can be modeled as the sum of several multidimensional damped sinusoids. The estimated frequencies and damping factors of multidimensional NMR data play important roles in determining protein structures. In this paper we present a high-resolution subspace method for estimating the parameters of NMR data. Unlike other methods, this algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(66 citation statements)
references
References 28 publications
0
66
0
Order By: Relevance
“…To facilitate the algorithm development, we express (1) in matrix form as (3) where , , and with , , and . From the regular structure of , it is straightforward to see that the noise-free data matrix can be represented as (4) where (5) and (6) are complex vectors which are characterized by and , and and , respectively. It is also observed that the elements in and satisfy the LP property: (7) and (8) where (9) and (10) On the other hand, can be decomposed using SVD as (11) where is the diagonal matrix of singular values of with while and are orthonormal matrices whose columns are the corresponding left and right singular vectors, respectively.…”
Section: Estimation For Damped Complex Tonementioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the algorithm development, we express (1) in matrix form as (3) where , , and with , , and . From the regular structure of , it is straightforward to see that the noise-free data matrix can be represented as (4) where (5) and (6) are complex vectors which are characterized by and , and and , respectively. It is also observed that the elements in and satisfy the LP property: (7) and (8) where (9) and (10) On the other hand, can be decomposed using SVD as (11) where is the diagonal matrix of singular values of with while and are orthonormal matrices whose columns are the corresponding left and right singular vectors, respectively.…”
Section: Estimation For Damped Complex Tonementioning
confidence: 99%
“…The is assumed to be a real zero-mean white Gaussian process with unknown variance . Expressing (37) in matrix form, we find that it can be decomposed as in (4) The former is constructed from and while the latter is a function of . Pre-multiplying both sides of (55) by yields (58)…”
Section: Estimation For Damped Complex Tonementioning
confidence: 99%
See 1 more Smart Citation
“…Parameter estimation from bidimensional (2-D) and multidimensional (N -D) signals finds many applications in signal processing and communications such as magnetic resonance (NMR) spectroscopy [5], wireless communication channel estimation, antenna array processing, radar and medical imaging [1]. In these applications, signals are modeled by a superposition of damped or undamped N -D complex exponentials.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the standard one-dimensional signal model [4]- [6], multi-dimensional spectral estimation [7] in fact has many applications such as array processing [8]- [9], nuclear magnetic resonance (NMR) spectroscopy [10], wireless communication channel estimation [11]- [12] as well as detection and localization of multiple targets using multiple-input multiple-output (MIMO) radar [13].…”
mentioning
confidence: 99%